PHENOMENOLOGICAL STUDY OF THE RELEVANCE OF KI HAJAR DEWANTARA'S PHILOSOPHY IN THE CONTEXT OF FAMILY EDUCATION IN THE VUCA TRANSITION TOWARDS BANI - Muhammad Isnaeni; Heri Yusuf Muslihin; Dian Indihadi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
The VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era is transforming into BANI (Brittle, Anxious, Non-linear, Incomprehensible), presenting complex challenges for family education. This research aims to analyze the relevance of Ki Hajar Dewantara's philosophy (Ing Ngarso Sung Tuladla; Ing Madya Mangun Karsa; Tut Wuri Handayani) in the context of family education (child-rearing behavior) in the era of VUCA transition towards BANI through various philosophical perspectives. This research uses a qualitative approach with a literature study method (library research) and phenomenological research type. Secondary data were collected from various relevant sources such as books, scientific journals, and articles. Data analysis was conducted using content analysis techniques and phenomenological interpretation, which included data reduction, data categorization, data interpretation, data synthesis, and phenomenological reflection. The research data is presented based on the perspective of the interpretive framework (Postpositivism, Constructivism, Transformative, Pragmatism, and Critical) and the framework of belief (Ontology, Epistemology, Axiology and Methodology) The results show that Ki Hajar Dewantara's philosophy has potential relevance in the context of family education in the era of VUCA transition to BANI. The concept of Ing Ngarso Sung Tulodho emphasizes the role of parents as role models. Ing Madya Mangun Karsa highlights the importance of building motivation and active participation of children. Tut Wuri Handayani underscores supporting and empowering children according to their potential. Ki Hajar Dewantara's philosophy offers a relevant guideline for family education in facing the complexity of the VUCA era towards BANI evidenced by a framework of beliefs and a framework of interpretation.